2015
DOI: 10.1186/s12913-015-0912-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of loss to follow-up in patients on antiretroviral treatment, South Africa, 2004–2012: a cohort study

Abstract: BackgroundThe number of Human Immunodeficiency Virus (HIV) infected people eligible for initiation on antiretroviral Therapy (ART) is increasing. ART programmatic success requires that patients who are taking ART remain on treatment and are followed up regularly. This study investigated factors associated with being lost to follow-up, in a cohort of patients enrolled in a pharmacovigilance study in South Africa.MethodsThis was a retrospective observational cohort study performed at one of the Medunsa National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 19 publications
11
75
3
Order By: Relevance
“…The annual time points reflect the WHO recommendations for VL testing to monitor for treatment failure 8 . We have chosen to include data up to three years after ART initiation to minimise LTFU as patient retention has been shown to decrease to 65% at three years 9 . As different sites have different definitions of LTFU, patients in this study were considered to be LTFU according to the LTFU indicator provided in each regional database.…”
Section: Methodsmentioning
confidence: 99%
“…The annual time points reflect the WHO recommendations for VL testing to monitor for treatment failure 8 . We have chosen to include data up to three years after ART initiation to minimise LTFU as patient retention has been shown to decrease to 65% at three years 9 . As different sites have different definitions of LTFU, patients in this study were considered to be LTFU according to the LTFU indicator provided in each regional database.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified the factors associated with LTFU among persons on ART to include younger age, male sex, single, divorced or separated marital status, illiteracy, having no income-generating occupation, non-disclosure of HIV diagnosis, stigma, distance to health facilities, poor nutrition, normal body mass index, pregnancy, high or low CD4 count, tuberculosis co-infection, advanced clinical staging, detectable viral load and adverse drug reactions [5,8,9,[13][14][15][16][17][18][19][20][21]. However, most of these studies employed retrospective LTFU definitions; to our knowledge, no studies have assessed factors associated with recurrent LTFU episodes from HIV programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Berheto et al and Honge et al classified patients as LTFU if they failed to pick their ART after 90 days from the last scheduled date [40,42], a similar definition to that used in our study. In the papers written by Berheto et al and Honge et al, an elevated risk of LTFU was noticeable in patients that had a baseline CD4 cell count of <200 cells/ml [37,39] while a similar risk was observed in patients with a CD4 cell count of >200 cells/ml by Mberi et al [41]. In comparison to our cohort, we categorized CD4 cell count as <350 cells/ml, 350-500 cells/ml and >500 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for the contrast could be differences in the determination of LTFU as well as the differing CD4 cell count thresholds used across the studies. A patient was classified LTFU if they had spent at least 180 days without picking their ART from the HIV clinic after a scheduled visit [41]. Berheto et al and Honge et al classified patients as LTFU if they failed to pick their ART after 90 days from the last scheduled date [40,42], a similar definition to that used in our study.…”
Section: Discussionmentioning
confidence: 99%